Does Reduction Mammaplasty Play a Role in Weight-Loss Motivation and Quality of Life Improvement in Symptomatic Macromastia Patients? - Mehmet Çeber (Turkish Journal of Plastic Surgery, 2016)
Objective: The purpose of this study was to evaluate whether reduction mammaplasty is a motivator for postoperative weight loss and to understand how this affected specific quality of life parameters. Material and Methods: All patients who underwent a reduction mammaplasty by the senior author at our department between April 2011 and January 2014 were contacted and invited to participate in a standardized telephonic questionnaire. The outcome questionnaire included data on whether the patients felt that the reduction mammaplasty was a motivator for weight loss and specific information regarding their pre- and postoperative weight and dress size. Additional data points queried included quality of life changes, exercise capacity, satisfaction, symptomatic relief (neck and back pain, intertrigo, shoulder grooving), and whether they would undergo the procedure again. Results: Forty-five women participated in the questionnaire. A total of 66.7% (n=30) participants stated that reduction mammaplasty was a motivator for future weight loss (group A), and 33.3% (n=15) participants felt that reduction mammaplasty was not a motivator for future weight loss. When the pre- and postoperative weights of women in group A were compared, there was a significant difference seen following reduction mammaplasty (p<0.001). Group B had a non-significant decrease in weight (p=0.23). The mean weight loss in group A was 6.66±1.44 kg) and group B was 1.13±2.16 kg. There was a statistically significant difference in weight loss between the groups (p<0.001). There was a statistically significant difference between pre- and postoperative body mass index (BMI) in group A (p<0.001), whereas the difference was not statistically significant in group B. There was a statistically significant difference in BMI between the groups (p<0.001). There was a statistically significant decrease in dress size in group A and B (p<0.001). There was a 73% improvement in postoperative exercise in group A and 13.3% improvement in group B. Conclusion: Reduction mammaplasty not only improves the patients’ symptoms of macromastia and their breast shape but also is a motivator for postoperative weight loss.